Do We Need a Gravimetric Geoid or a Model of the Australian Height Datum to Transform GPS Heights in Australia? - Featherstone, Will (The Institution of Surveyors, Australia Inc., 1998)
A proposal is made to use a model of the Australian Height Datum (AHD) instead of the classical geoid to provide a more direct transformation of Global Positioning System (GPS) ellipsoidal heights to the AHD. This approach avoids post-survey adjustment of the GPS-AUSGEOID-derived heights in order to align them with existing AHD control. Alternatively, of course, the AHD could be redefined and readjusted such that it is more coincident with the classical geoid, thus allowing the use of a pure gravimetric geoid model in the height transformation. However, the cost and inconvenience associated with implementing a new national vertical datum in the near future render the proposed approach a more practical option in the interim.